HUBUNGAN RIWAYAT PERSALINAN DAN PARITAS DENGAN KEJADIAN PERDARAHAN ANTEPARTUM - Siti Patimah, Siti Patimah; Sitawati (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2023)
Antepartum hemorrhage is a complication that often occurs in pregnancy until just before delivery. Based on the theory of antepartum hemorrhage, there are several risk factors for pregnant women such as maternal age, parity, history of childbirth, and malnutrition. In 2020, the highest incidence of antepartum hemorrhage in the Kenanga Community Health Center working area was 54 people. This study aims to determine the factors associated with the incidence of antepartum hemorrhage in the Kenanga Community Health Center Work Area in 2023. This research uses an analytical survey research method with a